Paleohistology of Caraguatypotherium munozi (Mammalia, Notoungulata, Mesotheriidae) from the early late Miocene of northern Chile: A preliminary ontogenetic approach - Campos-Medina, Jorge; Montoya-Sanhueza, Germán; Moreno, Karen; Bostelmann Torrealba, Enrique; García, Marcelo (PloS one, 2023)
The Miocene Caragua fossil fauna in northern Chile contains a considerable number (7) of articulated partial skeletons tentatively assigned to Caraguatypotherium munozi (Notoungulata, Mesotheriidae), which presents up to 40% body size difference. Since either inter- and intra- specific wide size range has been observed in the Mesotheriidae family in general, we wanted explore the ontogenic stage signature of the sample, by carrying out the first comprehensive paleohistological description of the appendicular system in Notoungulata. Results show that: 1) they can be classified as subadults and adults, based on the presence of bone tissues typical of ceased somatic growth; 2) there is a notorious inter-skeletal variation on bone growth rates (skeletal modularity), particularly, the humerus showed a slower diameter growth and less remodelling than the femur, resulting as a better element for ontogenetic analyses; 3) marked cyclical growth is observed, characterised by fast early ontogenic continuous growth, and subsequent fast/slow stratified bone tissue layering. In general, such growth pattern suggests that C. munozi had a similar ontogenetic growth process as other modern mammals, that it should also be influenced by other sex-related, ecological and environmental factors. Likely related to the presence of rapid climatic variations, due to orogenic uplift and concomitant re-organization of the drainage processes along the western tectonic front of the Central Andes at that time.
Keywords: Animals; Chile; humerus; Phylogeny; Fossils; zkameněliny; Eutheria; Humerus; fylogeneze; savci; placentálové; Mammals; zvířata